IMPLEMENTASI PENDIDIKAN KARAKTER CINTA TANAH AIR PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM SISWA SEKOLAH MENENGAH ATAS ISLAM NUSANTARA - Arinda Farhany Istifa; Maskuri Bakri; Muhammad Sulistiono (Vicratina : Jurnal Ilmiah Keagamaan, 2022)
Character education is an effort to instill character values in students that includes components of knowledge, awareness or will, and action to implement the values of character education. The purpose of this study is to describe the planning, execution and results of love of country character education. To achieve this goal, the research was carried out using a type of qualitative research. The results of this study are 1) It can be said that the character planning of SMA Islam Nusantara Malang students in general is good or positive even though they come from different backgrounds. 2) The implementation of character in SMA Islam Nusantara Malang conforms to the vision of the school that wants to develop Islamic character based on Ahlusunnah Waljamaah Islam, which builds and develops science and technology, imtaq, as well as motivation and spirit student entrepreneur. 3) The results of the implementation of Islamic Religious Education in SMA Islam Nusantara Malang as an effort to form the character of love for the motherland of the students can be seen through the characters they show in their daily life at school.